LEGISLASI HUKUM ISLAM (Telaah terhadap Konsep Taqnin dalam Ranah Substantivistik dan Formalistik) - Moch Cholid Wardi (Research Institute and Community Engagement of IAIN MADURA, 2018)
Taqnin or known as legislation is a group of regulations with binding characteristic. Practically, the concept of Taqnin talks more about the substantial or formalization aspect so that it becomes the reason of the emergence of the debate on Taqnin or legislation in Islam in the context of Shari’a. Indonesia with Pancasila as an ideology has different characteristic with other majority moslems countries, although the majority of indonesians are Moslems. The ideology of the country is not shari’a but Pancasila. Therefore, there is a debate on groups about the islamic law of legislation between formalistic-normative group and substantivistic- cultural group.